38. STUDY ON DELIVERY METHODS AMONG FULL-TERM PRIMIPAROUS WOMEN AGED OVER 35 AT THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Background: Primiparous women over 35 years old have a higher risk of pregnancy and delivery complications.Objective: To study the delivery methods among full-term primiparous women aged over 35 at Thai Nguyen National Hospital in 2024.Methods: A descriptive cross-sectional study was conducted on 45 primiparous women aged 35 and above with singleton, live fetuses in cephalic presentation at term who delivered at Thai Nguyen National Hospital from January 1 to December 31, 2024.Results: The mean maternal age was 37.8 ± 2.7 years, and the mean gestational age was 38 weeks and 3 days ± 1 week and 2 days. The majority of patients (88.9%) were admitted before labor onset. The cesarean section rate was 88.9%, while vaginal deliveries with episiotomy accounted for 11.1%.Conclusion: The cesarean section rate is high among full-term primiparous women over 35 years old.
Keywords: Cesarean section; primiparous; labor